Formulation of objective indices to quantify machine failure risk analysis for interruptions in radiotherapy. Issue 1 (16th December 2020) - Kawahara, Daisuke; Nakano, Hisashi; Saito, Akito; Ochi, Yusuke; Nagata, Yasushi
Abstract: Objectives: To evaluate the effect of interruption in radiotherapy due to machine failure in patients and medical institutions using machine failure risk analysis (MFRA). Material and methods: The risk of machine failure during treatment is assigned to three scores (biological effect, B ; occurrence, O ; and cost of labor and repair parts, C ) for each type of machine failure. The biological patient risk (BPR) and the economic institution risk (EIR) are calculated as the product of B and O ( B × O ) and C and O ( C × O ), respectively. The MFRA is performed in two linear accelerators (linacs). Result: The multileaf collimator (MLC) fault has the highest BPR and second highest EIR. In particular, TrueBeam has a higher BPR and EIR for MLC failures. The total EIR in TrueBeam was significantly higher than that in Clinac iX. The minor interlock had the second highest BPR, whereas a smaller EIR. Meanwhile, the EIR for the LaserGuard fault was the highest, and that for the monitor chamber fault was the second highest. These machine failures occurred in TrueBeam. The BPR and EIR should be evaluated for each linac. Further, the sensitivity of the BPR, it decreased with higher T 1 / 2 and α/β values. No relative difference is observed in the BPR for each machine failure when T 1 / 2 and α / β were varied. Conclusion: The risk faced by patients and institutions in machine failure may be reduced using MFRA. Advances in knowledge: For clinical radiotherapy, interruption can occur from unscheduled downtime with machine failures. Interruption causes sublethal damage repair. The current study evaluated the effect of interruption in radiotherapy owing to machine failure on patients and medical institutions using a new method, that is, machine failure risk analysis.